Social Determinants of Health in Non-communicable Diseases Case Studies from Japan - Kondo, Katsunori (Springer Series on Epidemiology and Public Health,, 2020)
This open access book is the first compilation that reviews a wide range of social determinants of health (SDHs) for non-communicable diseases (NCDs) and healthy ageing in Japan. With the highest life expectancy and the largest elderly population in the world, Japan has witnessed health inequality by region and social class becoming more prevalent since the 2000s. The first half of this volume describes in detail major NCDs, such as cancers, heart and kidney diseases, diabetes, stroke, and metabolic syndrome. The second half, on the other hand, explores various SDHs relating to healthy ageing. All chapters review and focus on SDHs, particularly health inequality associated with socio-economic status and social capital, which are widely addressed in the field of social epidemiology. The book makes the argument that "Health for All" advocated by the WHO should be implemented based on social justice and benefits for the greater society. Public health researchers and policymakers, both in Japan and other nations, will gain scientific evidence from this book to prepare for the coming era as ageing becomes a global issue. Katsunori Kondo is Professor of Social Epidemiology and Health Policy, Center for Preventive Medical Sciences and the Graduate School of Medicine, Chiba University, Japan. He is also Head of Department of Gerontological Evaluation at the Center for Gerontology and Social Science, National Center for Geriatrics and Gerontology. .